Image Cytometry Based Detection of Aneuploidy by Fluorescence In situ Hybridization in Suspension - Minderman, Hans (Cytometry A, 2012)
Cytogenetic abnormalities are important diagnostic and prognostic criteria for hematologic malignancies. Karyotyping and Fluorescent In Situ Hybridization, (FISH), are the conventional methods by which these abnormalities are detected. The sensitivity of these microscopy-based methods is limited by the abundance of the abnormal cells in the samples and therefore these analyses are commonly not applicable to minimal residual disease stages. A flow cytometry-based imaging approach was developed to detect chromosomal abnormalities following FISH in suspension (FISH-IS) which enables the automated analysis of several log-magnitude higher number of cells compared to the microscopy-based approaches. The present study demonstrates the applicability of FISH-IS for detecting numerical chromosome aberrations, establishes accuracy and sensitivity of detection compared to conventional FISH, and feasibility to study procured clinical samples of acute myeloid leukemia (AML). Male and female healthy donor peripheral blood mononuclear cells hybridized with combinations of chromosome enumeration probes (CEP) 8, X and Y served as models for disomy, monosomy, and trisomy. The sensitivity of detection of monosomies and trisomies amongst 20,000 analyzed cells was determined to be 1% with a high level of precision. A high correlation (R(2)=0.99) with conventional FISH analysis was found based on the parallel analysis of diagnostic samples procured from 10 AML patients with trisomy 8 (+8). Additionally, FISH-IS analysis of samples procured at the time of clinical remission demonstrated the presence of residual (+8) cells indicating that this approach may be used to detect minimal residual disease and associated chromosomal defects.